Surface modification of polybenzoxazines by electrochemical hydroquinone-quinone switch. (5th January 2021) - Kaya, Gizem; Kiskan, Baris; Isci, Recep; Eroglu, Mehmet S.; Ozturk, Turan; Yagci, Yusuf
Graphical abstract: Highlights: Electro-responsive polybenzoxazine based high performance thermoset surfaces were prepared. The surface morphology of the prepared polybenzoxazines films were altered electrochemically. Hydrophilicity of the films could be changed via redox process. Abstract: In this study, we report a novel strategy to fabricate electro-responsive polybenzoxazine based high performance thermoset surfaces. Three structurally different benzoxazines form simple chemicals such as hydroquinone, formaldehyde, and corresponding primary amines were prepared and coated as thin films by solvent casting on ITO electrodes. Subsequently, they were cured by thermally activated ring opening polymerization. The structural characteristics and thermal behavior of the benzoxazines were evaluated by FTIR, 1 H NMR and DSC, respectively. The electrochemical properties of the films were investigated by using cyclic voltammetry. Finally, the surface properties of the films after redox processes were examined by contact angle measurements, scanning electron microscopy (SEM) and atomic force microscopy (AFM). This work presents a straightforward electrochemical method for tuning surface morphology and hydrophilicity by redox process through hydrogen bonding interactions.